Hypermedia applications for children educators - Amante, Lúcia (2020)
The main goal of the two applications is to to support adult learning in self-learning contexts namely children educators, teachers, psychologists, and general educational scientists, as well as professionals in artistic fields. The application design promotes interaction and different paths to the student.